An Introduction to Information Network Modeling Capabilities, Utilizing Graphs - Koukaras, Paraskevas; Rousidis, Dimitrios; Tjortjis, Christos (Metadata and Semantic Research, 2021)
This paper presents research on Information Network (IN) modeling using graph mining. The theoretical background along with a review of relevant literature is showcased, pertaining the concepts of IN model types, network schemas and graph measures. Ongoing research involves experimentation and evaluation on bipartite and star network schemas, generating test subjects using Social Media, Energy or Healthcare data. Our contribution is showcased by two proof-of-concept simulations we plan to extend.